1996
DOI: 10.18388/abp.1996_4458
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenesis in virgin and mated females of the mealworm beetle, Tenebrio molitor.

Abstract: A comparison between vitellogenesis in virgin and mated females of Tenebrio molitor showed significant differences at each investigated developmental stage. Yolk protein deposition in oocytes, measured as an increase in their size parameters (length, width, and volume), proceeded much faster and was more efficient in mated females as compared to virgins. In fertilized females the gonadotropic cycle showed a cyclicity with an eight-day period while virgin females finish their vitellogenic stage after the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1), although only two of these would be supported by published observations of cleavage products. Both Harnish & White (1982) and Webb & Hurd (1995) detected large subunits of 154 and 145 kDa and small subunits of 56 and 45 kDa, while Michalik et al . (1996) detected a single large subunit of 158 kDa and two small subunits of 56 and 45 kDa.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1), although only two of these would be supported by published observations of cleavage products. Both Harnish & White (1982) and Webb & Hurd (1995) detected large subunits of 154 and 145 kDa and small subunits of 56 and 45 kDa, while Michalik et al . (1996) detected a single large subunit of 158 kDa and two small subunits of 56 and 45 kDa.…”
Section: Discussionmentioning
confidence: 90%
“…1), although only two of these would be supported by published observations of cleavage products. Both Harnish & White (1982) and Webb & Hurd (1995) detected large subunits of 154 and 145 kDa and small subunits of 56 and 45 kDa, while Michalik et al (1996) detected a single large subunit of 158 kDa and two small subunits of 56 and 45 kDa. We note that both T. molitor and A. grandis have recognizable R/KXXR motifs in almost identical locations (A. grandis, RRFR [359][360][361][362] or RFRR [360][361][362][363] ; T. molitor, KSSR [365][366][367][368] or RTKR [368][369][370][371] ).…”
Section: Discussionmentioning
confidence: 98%
“…The densitometric analysis revealed that two polypeptides with molecular masses of 150 and 180 kDa are nearly ab-sent in peptide-treated females while two other polypeptides with molecular masses of 47 and 130 kDa (Fig. 4) but also in regulating oviposition and ovulation (Michalik et al, 1996;Graham et al, 1996;Cole et al, 2003;Heming, 2003). Evidently, juvenile hormone is only one of the hormones controlling gonadal development in Tenebrio.…”
Section: Discussionmentioning
confidence: 93%
“…Elevated JH concentrations typically suppress 20E synthesis [44]. In the captivating world of beetles, as part of the Coleoptera order, the JH takes center stage, driving vitellogenesis within the fat body [45,46]. Vitellogenesis involves the synthesis and accumulation of yolk proteins in maturing oocytes, which are crucial for nourishing the embryo post-fertilization [47].…”
Section: Sterol Hormone 20e Biosynthesismentioning
confidence: 99%